THE EFFECT OF CONTENT CREATOR ENDORSEMENTS ON MSME CONSUMERS' PURCHASING DECISIONS - Nurfaisah Nurfaisah; Abdul Nasser Hasibuan; Budi Gautama (Nurul Jadid University, 2025)
In the digital era, marketing strategies have shifted from conventional media to more dynamic and interactive social media. One of the strategies that is growing rapidly is the use of endorsements by content creators to influence consumer purchase decisions. This study aims to find out the extent of the influence of content creator endorsements on purchase decisions on MSME products. This study used a quantitative approach with multiple linear regression method and involved 75 respondents, which were determined based on the Malhotra formula (at least five times the number of indicators). The results showed that endorsements had a positive and significant influence on purchase decisions, with a significance value of 0.000 and a regression coefficient of 0.705. These findings indicate that collaboration with content creators can be an effective and efficient promotional strategy for MSMEs in reaching a wider market through social media.